2018
DOI: 10.1002/ldr.2887
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐efficiency and reliability of two methods for soil organic C accounting

Abstract: Sequestering organic carbon (C) in soil can help to combat land degradation, improve food security, and mitigate greenhouse gas emissions and climate change. But we need reliable, cost‐efficient methods to assess, monitor, and verify the change. Here, we compared two methods for the direct measurement of soil organic C stocks and for monitoring the change. Our aims were to quantify the soil organic C stock in two carbon estimation areas, under cropping and grazing, using composite sampling with two designs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Forests and production forestry were excluded because we lack adequate data to support simulations under these land uses. The C fractions, clay content and AWC were estimated with visible-near-infrared spectra (Viscarra Rossel and Webster, 2012;Viscarra Rossel et al, 2015). Maximum air temperature, minimum air temperature, precipitation and pan evaporation are also required to run the model.…”
Section: Data Compilation and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Forests and production forestry were excluded because we lack adequate data to support simulations under these land uses. The C fractions, clay content and AWC were estimated with visible-near-infrared spectra (Viscarra Rossel and Webster, 2012;Viscarra Rossel et al, 2015). Maximum air temperature, minimum air temperature, precipitation and pan evaporation are also required to run the model.…”
Section: Data Compilation and Synthesismentioning
confidence: 99%
“…In this context, the development of robust frameworks for soil organic C modelling and simulation to synthesise and integrate measurements and datasets with models is critical (Harden et al, 2018;Ogle et al, 2010;Paustian et al, 1997;Smith et al, 2020). Their development should also allow for their efficient updating, with new measurements, data and models, as they become available (Viscarra Rossel and Brus, 2018;England and Viscarra Rossel, 2018;Smith et al, 2020) and enable a more systematic approach for calibration and validation, making simulations more reliable and reproducible.…”
Section: Introductionmentioning
confidence: 99%
“…et al (2016b) showed that the 5 sensing system can be used to accurately baseline soil C stocks for accounting purposes. The system was use to derive baseline estimates of soil organic C stocks (Viscarra Rossel, R.A. et al, 2016b) and its efficiency and reliability for soil C accounting was assessed by Viscarra Rossel, R. A. and Brus (2018). They found that compared to more conventional methods that use composite sampling and laboratory analysis, sensing with the SCANS is more cost-efficient in that it provides a good balance between accuracy and cost.…”
Section: Aga Backscatter Bulk Densitymentioning
confidence: 99%
“…Their measurements are accurate and cost-efficient (Viscarra Rossel, R. A. and Brus, 2018). While there are several reviews on the use of sensors for measuring soil organic C concentration (e.g Bellon-Maurel and McBratney, 2011;Izaurralde et al, 2013;Reeves et al, 2012;Stenberg et al, 2010;Viscarra Rossel, R.A. et al, 2011), few studies report on sensors for measuring bulk density or gravel (Lobsey and Viscarra Rossel, 2016;Fouinat et al, 2017), or report on the integration of 5 sensing methods for the purpose of soil organic C accounting.…”
mentioning
confidence: 99%
“…There is a wide range of statistical tools available for multivariate modelling of soil properties. Ongoing research is continuously evaluating new tools at the same time striving to clarify the viability of application of VIS-NIR-SWIR soil spectroscopy in specific scenarios (e.g., Gholizadeh, Saberioon, Carmon, Boruvka, & Ben-Dor, 2018;Ogen, Neumann, Chabrillat, Goldshleger, & Ben-Dor, 2018;Ostovari et al, 2018;Terra, Demattê, & Viscarra Rossel, 2018;Viscarra Rossel & Brus, 2018).…”
mentioning
confidence: 99%